Oral health-seeking behaviour of persons living with diabetes mellitus attending a tertiary hospital in south west Nigeria - Falokun, Ifeoluwa B.; Olopade, Oluwarotimi B.; Adekanmbi, Oluwadolapo G.; Odeniyi, Ifedayo A.; Esenwa, Ogochukwu P.; Inya, Emmanuel O.; Ede, Obiamaka J. (International Journal Of Community Medicine And Public Health, 2025)
Background: Diabetes mellitus is associated with a wide array of oral health complications with research revealing a high prevalence of oral health issues among diabetic individuals. This study evaluated the oral health-seeking behavior (OHSB) and awareness of oral complications associated with type 2 diabetes mellitus (T2DM) among patients diagnosed with T2DM. Methods: A cross-sectional study was conducted involving 158 T2DM patients. Using interviewer-administered questionnaires, information was collected on participants’ awareness of the relationship between T2DM and oral health, their perceived importance of seeking dental care, and their dental visit history since diagnosis. Results: Only 30.4% of respondents were aware of a connection between T2DM and oral health, with 28.5% recognizing that poor glycemic control could exacerbate gum disease. Approximately half of the respondents (51.9%) understood the importance of regular dental check-ups for individuals with diabetes, while 41.1% were unaware of its significance. A large majority (82.9%) had never been informed by their physician about the need for regular dental check-ups. Dental visits were infrequent, with 43% having visited a dentist post-diagnosis and only 20.3% within the past year. Conclusions: T2DM patients demonstrate inadequate awareness of oral health complications and poor OHSB. Enhanced collaboration between physicians and dentists is necessary to improve referrals and oral health education, potentially mitigating oral complications in this vulnerable population.